2020
DOI: 10.3389/fnmol.2020.560020
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic Astrocyte-Derived Neurotrophic Factor (MANF) Regulates Neurite Outgrowth Through the Activation of Akt/mTOR and Erk/mTOR Signaling Pathways

Abstract: Neurite outgrowth is essential for brain development and the recovery of brain injury and neurodegenerative diseases. In this study, we examined the role of the neurotrophic factor MANF in regulating neurite outgrowth. We generated MANF knockout (KO) neuro2a (N2a) cell lines using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 and demonstrated that MANF KO N2a cells failed to grow neurites in response to RA stimulation. Using MANF siRNA, this finding was confirmed in human SH-SY5Y neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…After injury in mice, GDNF peaks around 7 days, and BDNF levels peak around 2–3 weeks [ 43 ]. Trophic factors involved in neurite outgrowth, cytoprotection, and neuronal survival such as mesencephalic astrocyte-derived neurotrophic factor (MANF) have also been reported to increase after peripheral nerve injury similar to the upregulation we observed in our analyses [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 83%
“…After injury in mice, GDNF peaks around 7 days, and BDNF levels peak around 2–3 weeks [ 43 ]. Trophic factors involved in neurite outgrowth, cytoprotection, and neuronal survival such as mesencephalic astrocyte-derived neurotrophic factor (MANF) have also been reported to increase after peripheral nerve injury similar to the upregulation we observed in our analyses [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 83%
“…These pathways were directly related to neurite development. Also, the enriched items included some pathways which have been demonstrated closely related to neurite development, such as the PI3K-AKT signaling pathway (Zhao et al, 2020), mTOR signaling pathway (Wen et al, 2020), cGMP-PKG signaling pathway (Sun et al, 2020), thyroid hormone signaling pathway (Poddar et al, 1996), and calcium signaling pathway (Zhao et al, 2019; Figure 2E).…”
Section: Rf-emf Exposure Induced Transcriptomic Changes Related To Neurite Outgrowthmentioning
confidence: 99%
“…Several studies also showed MANF’s ability to induce neurite outgrowth. For example, MANF was shown to promote neurite outgrowth in DA neurons and N2a cells [ 2 , 65 ]. Additionally, MANF was shown to be essential for neurite extension in the developing mouse cortex.…”
Section: Discussionmentioning
confidence: 99%